Голубые ангелы: [16+] / Чингиз Абдуллаев - Абдуллаев Чингиз (Лучшие романы о сыщике Дронго)
Экземпляры: ф. оиф (20141111) / Инвентарный номер: 49293 / Цена: 83.00 / Авт.знак: А 13 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6